Incidence and progression to cirrhosis of new hepatitis C virus infections in persons living with human immunodeficiency virus. (April 2017) - ,; d'Arminio Monforte, A.; Andreoni, M.; Angarano, G.; Antinori, A.; Castelli, F.; Cauda, R.; Di Perri, G.; Galli, M.; Iardino, R.; Ippolito, G.; Lazzarin, A.; et al.
Abstract: Objective: To estimate the incidence of hepatitis C virus (HCV) seroconversion and the risk of severe fibrosis/cirrhosis in HCV seroconverters among persons with human immunodeficiency virus (HIV) infection. Methods: We analysed data on 4059 persons with HIV enrolled in a cohort study in Italy. Results: Incidence rate of seroconversion was 0.6/100 person-years overall, and drug users and men-who-have-sex-with-men were at highest risk. The cumulative risk of progression to severe fibrosis/cirrhosis was 30% by 10 years after seroconversion. Conclusions: New HCV infections have a rapidly progressive course in this population. Persons with HIV and HCV superinfection should be prioritized for treatment with anti-HCV direct-acting antivirals.